Long-Term Effects on the Lipidome of Acute Coronary Syndrome Patients - Kosek, Vít; Hajšl, Martin; Bechyňská, Kamila; Kučerka, Ondřej; Suttnar, Jiří; Hlaváčková, Alžběta; Hajšlová, Jana; Malý, Martin (Metabolites, 2022)
Lipids modified by oxidative stress are key players in atherosclerosis progression. Superimposed thrombosis with subsequent closure of the coronary artery leads to the clinical manifestation of acute coronary syndrome (ACS). While several studies focusing on alterations in lipid metabolism in the acute phase have been conducted, no information is available on patients' lipidome alterations over longer time periods. In the current follow-up study, we analyzed plasma samples obtained from 17 patients three years after their ACS event (group AC). Originally, these patients were sampled 3-5 days after an index event (group B). Lipidome stability over time was studied by untargeted lipidomics using high performance liquid chromatography coupled to high resolution mass spectrometry (UHPLC-HRMS). Multi-dimensional statistics used for data processing indicated that plasmalogen lipids were the most prominent lipids separating the above patient groups and that they increased in the follow-up AC group. A similar trend was observed for lysophosphatidylethanolamine (LPE) and phosphatidylethanolamine (PE). The opposite trend was observed for two fatty acyls of hydroxy fatty acid (FAHFAs) lipids and free stearic acid. In addition, a decrease in the "classic" oxitadive stress marker, malondialdehyde (MDA), occurred during the follow-up period. Our findings present unique information about long-term lipidome changes in patients after ACS.
Keywords: acute coronary syndrome; lipidomics; high resolution mass spectrometry; stroke